2013
DOI: 10.1371/journal.pone.0069314
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Analysis of the Late Otocyst Stage Mouse Inner Ear by Transuterine Microinjection of A Retroviral Vector Encoding Alkaline Phosphatase and an Oligonucleotide Library

Abstract: The mammalian inner ear subserves the special senses of hearing and balance. The auditory and vestibular sensory epithelia consist of mechanically sensitive hair cells and associated supporting cells. Hearing loss and balance dysfunction are most frequently caused by compromise of hair cells and/or their innervating neurons. The development of gene- and cell-based therapeutics will benefit from a thorough understanding of the molecular basis of patterning and cell fate specification in the mammalian inner ear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The morphological steps of DT that we see for HC regeneration in explanted mammalian postnatal vestibular epithelia are similar to early development of HCs from progenitor cells or SCs described for the basilar papilla, avian homologue of the cochlea (Jacques et al, 2012). HCs and SCs are derived from a common pool of progenitor cells (Fekete et al, 1998;Jiang et al, 2013). There is a possibility that a subgroup of the SCs retain the ability to transdifferentiate into HCs.…”
Section: Discussionsupporting
confidence: 71%
“…The morphological steps of DT that we see for HC regeneration in explanted mammalian postnatal vestibular epithelia are similar to early development of HCs from progenitor cells or SCs described for the basilar papilla, avian homologue of the cochlea (Jacques et al, 2012). HCs and SCs are derived from a common pool of progenitor cells (Fekete et al, 1998;Jiang et al, 2013). There is a possibility that a subgroup of the SCs retain the ability to transdifferentiate into HCs.…”
Section: Discussionsupporting
confidence: 71%
“…Similar results have recently been observed using single cell photo-conversion of genetically encoded fluorescent tracers (Sapede, et al, 2012). Another recent study involving single cell retroviral lineage tracing in mouse failed to find common progenitors for neurons and hair cells (Jiang, et al, 2013); however it should be stressed that the age of labeling in this study (embryonic day 11) was quite late relative to the appearance of the neural-sensory competent domain, and that the number of retroviral clones analyzed in this study was quite small and may have been insufficient to capture rare clones containing both cell types. These studies show that the progenitors for sensory derivatives (hair cells and supporting cells) and neurons can differentiate in close proximity to one another, and that multi-potent cells capable of generating neurons, hair cells, or supporting cells can be identified at low frequencies.…”
Section: Lineage Relationships Between Neurons and Sensory Cells Omentioning
confidence: 62%
“…Force-plate posturography has been a common method used to assess postural control [12] measuring anteroposterior (AP) and mediolateral (ML) displacement of the center of pressure (CoP). A recent study [8] reported that the spatial magnitude of sway is affected by the gaze target distance in older adults, also showing that the width of the multifractal spectrum (a measure of temporal dynamics) is greater for older adults when compared with younger adults. Accordingly, Mufano, Wade, Stergiou and Stoffregenet [13] evaluated the kinematics of the CoP, regarding the amount of sway and the multifractality, in elderly people standing on a ship at sea (that departed from Nassau, Bahamas) when looking to the nautical horizon.…”
Section: Highlight By Luís Silvamentioning
confidence: 97%
“…Tendon abnormalities have also been described in some inherited metabolism disorders, such as Alkaptonuria which leads to a reduction in the structural integrity of collagen and increases rupture. Recently, Depreux et al used a novel in utero gene transfer method [7,8] for delivery of active antisense oligonucleotides (ASOs) into amniotic cavity of mouse embryo [9]. The amniotic cavity surrounding the fetus could serve as an ideal drug reservoir.…”
Section: Gene Therapy Strategies Could Improve Tendon Healing and Benmentioning
confidence: 99%